Regional variations in plantar fascia elasticity and their association with pain in plantar fasciitis: a cross-sectional study - Jiping Zhou; Yuyi Lin; Jiehong Zhang; Weiyi Pan; Chunlong Liu; Zhijie Zhang; Yulong Wang (Scientific Reports)
Abstract The aim of this study was to evaluate the relationship between plantar fascia (PF) elasticity, pain, visual analog scale (VAS) score, and plantar fascia thickness (PFT) in adults with plantar fasciitis (PFis). PF elasticity and PFT were measured in 40 subjects by ultrasonic shear wave elastography (USWE), and their VAS score and localized pressure pain threshold (PPT) were determined. Then, the correlations between PF elasticity and PFT, VAS score, and PPT were analyzed. PF elasticity was significantly lower in the PFis group than in the asymptomatic group (P < 0.001). PF elasticity at the point of calcaneus insertion was significantly lower in the PFis group (− 40.35% ± 9.81%, P < 0.001) but significantly higher in the asymptomatic group (26.69% ± 35.30%, P = 0.018) than that at 1 cm from this point. A significant correlation was detected between PF elasticity and both PPT and VAS scores. In terms of pain intensity, PPT and VAS scores showed a significant correlation (r =  − 0.921, P < 0.001). PF elasticity in different areas in patients with PFis was associated with pain intensity in terms of both PPT and VAS scores but not with PFT. USWE is a useful system for providing supplemental information in the diagnosis of PFis and provides quantitative parameters for monitoring therapy. Critical relevance statement USWE examination may exert a guiding impact on the pretreatment and posttreatment evaluation of patients with PFis.